Effect of Effective Microorganisms (EM) on the Growth Parameters of Fayoumi and Horro Chicken - Wondmeneh, E.; Getachew, T.; Dessie, Tadelle (2011)
The finding shows that: (1) EM supplementation had no observable effect on mortality, weight gain and FCR in both breeds but Fayoumi had inherently higher body weight than Horro. This study did not consider the cellular arm of the immune response and EM response to infections with specific pathogens was not investigated, collectively demanding further research in these and other issues if EM has to be used as good feed additive.